PENINGKATAN HASIL BELAJAR PKn MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING PADA SISWA KELAS V SD INPRES NIPA-NIPA KOTA MAKASSAR - Syam, Fitrawati; Pillang, Abd. Rahman; Hamid, Sundari; Arsyad, Susalti Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research was a Class Action Research. The problem in this study was the low learning outcomes of Civics students in grade V SD Inpres Nipa-Nipa. The purpose of this study was to describe the use of the Snowball Throwing Type Cooperative method in improving PKn learning outcomes for Grade V students of SD Inpres Nipa-Nipa. The hypothesis of this study was through the use of the Cooperative Type Snowball Throwing method, the PKn learning outcomes of the fifth grade students of SD Inpres Nipa-Nipa Makassar City on the subject of the Central and Regional Legislation Regulations can be improved. This research was carried out on fifth grade students of SD Inpres Nipa-Nipa in the academic year 2017/2018 and the number of students was 30 people. This research data was obtained from the test results of learning to see the success of student learning after learning using observation sheets for teachers and students for the conditions of the implementation of actions and teacher reflection journals. The procedure of this study consists of: (1) planning, (2) implementation of actions, (3) observation and evaluation, and (4) reflection. From the data exposure and discussion obtained the conclusion of learning by using audio-visual media can improve student learning outcomes PKn, where there was an increase in the average value of learning outcomes from 64.5 in the first cycle to 86.66 in cycle II and the completeness of learning outcomes of 36 , 66% or as many as 11 of 30 students whose grades reached the KKM in the first cycle increased to 96.66% or as many as 29 of 30 students whose grades reached the KKM in the second cycle.